Social Well-being as a Criterion of Fiscal Policy Efficiency; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Gromova A. S. Anna Sergeevna (2017, 2017)
Title screen